What Is the Role of AI in Hypertension Management? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Hypertension, or high blood pressure, is a major global health concern and a leading cause of cardiovascular disease and premature death [1]. Despite the ava...
Keywords: AI in Cardiology; Hypertension; Management; Artificial Intelligence; Machine Learning; Digital Health